Emotion Dysregulation and Inflammation in African-American Women with Type 2 Diabetes. (17th July 2016) - Powers, Abigail; Michopoulos, Vasiliki; Conneely, Karen; Gluck, Rachel; Dixon, Hayley; Wilson, Joseph; Jovanovic, Tanja; Pace, Thaddeus W. W.; Umpierrez, Guillermo E.; Ressler, Kerry J.; Bradley, Bekh; Gillespie, Charles F.
Abstract : C-reactive protein (CRP), a marker of systemic inflammation, has been associated with major depressive disorder (MDD) and posttraumatic stress disorder (PTSD). Emotion dysregulation is a transdiagnostic risk factor for many psychological disorders associated with chronic inflammatory state. The objective of this study was to determine whether inflammation is associated with emotion dysregulation in women with type 2 diabetes mellitus (T2DM). We examined associations between trauma exposure, MDD, PTSD, emotion dysregulation, and CRP among 40 African-American women with T2DM recruited from an urban hospital. Emotion dysregulation was measured using the Difficulties in Emotion Regulation Scale. PTSD and MDD were measured with structured clinical interviews. Child abuse and lifetime trauma load were also assessed. Analyses showed that both emotion dysregulation and current MDD were significantly associated with higher levels of CRP (p < 0.01 ). Current PTSD was not significantly related to CRP. In a regression model, emotion dysregulation was significantly associated with higher CRP (p < 0.001 ) independent of body mass index, trauma exposure, and MDD diagnosis. These findings suggest that emotion dysregulation may be an important risk factor for chronic inflammation beyond already known risk factors among women with T2DM, though a causal relationship cannot be determined from this study.